PEMANFAATAN LAHAN PASCA TAMBANG TIMAH DENGAN BUDIDAYA SAWI - Lestari, Tri A; Apriyadi, Rion; Ulfa, Dewi Ratna (Perhimpunan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Culture crop technology with ameliorant and mulch can fulfill nutrients to improve growth of mustard on post tin mining land. This research aimed to know the effect of various ameliorant and mulch for growth of mustard on post tin mining land. The method used was experimental method with factorial completely randomize design with four replications. First factor was type of ameliorant, consist of compost, and cow manure. The second factor was type of mulch, consist of no mulch, reed mulch, and black silver plastic mulch. The results showed that type of ameliorant significantly affected number of leave, root volume, root wet weight and root dry weight. Type of mulch significantly affected plant height, number of leave, shoot wet weight and root dry weight. Interaction of ameliorant and mulch significantly affected plant height, number of leave, root volume, shoot wet weight, root wet weight and root wet weight. Compost with black silver plastic mulch tended to give better results for growth of mustard on post tin mining land.